QUALITY OF LIFE FOR MEN IN THE 21ST CENTURY (CIPEEX, 2024)
QUALITY OF LIFE IS A BROAD CONCEPT THAT REFERS TO AN INDIVIDUAL'S OVERALL WELL-BEING IN VARIOUS ASPECTS OF THEIR LIFE. THIS CONCEPT TAKES INTO ACCOUNT NOT ONLY PHYSICAL HEALTH BUT ALSO EMOTIONAL, SOCIAL, ECONOMIC, AND ENVIRONMENTAL ASPECTS (PHILLIPS, 2006). BY USING THE SF-36 QUESTIONNAIRE, WE SOUGHT TO ASSESS THE CURRENT SITUATION OF A SPECIFIC PERCENTAGE OF A PARTICULAR POPULATION. THE FOCUS WAS ON IDENTIFYING THE QUALITY OF LIFE IN MEN OVER 18 YEARS OLD, BASED ON THEIR CURRENT PERSPECTIVE AND THAT OF ONE YEAR AGO, WITH AN OVERALL VIEW OF THEIR PSYCHOLOGICAL STABILITY, PHYSICAL CONDITION, AND ABILITY TO LIVE IN SOCIETY. THE RESEARCH WAS CONDUCTED USING THE SF-36 QUESTIONNAIRE, EXCLUSIVELY ADMINISTERED TO BRAZILIAN MEN AGED 18 YEARS OR OLDER. AS A RESULT OF AN EXTENDED AND SPECIFIC TIMEFRAME, A TOTAL OF 30 RESPONSES TO THE SF-36 QUESTIONNAIRE WERE SELECTED. THE STUDY CONSIDERED A MEASURE OF QUALITY OF LIFE COMPOSED OF 11 QUESTIONS AND 36 ITEMS, ENCOMPASSING EIGHT DISTINCT COMPONENTS: FUNCTIONAL CAPACITY, PHYSICAL ASPECTS, PAIN, GENERAL HEALTH STATUS, VITALITY, SOCIAL ASPECTS, EMOTIONAL ASPECTS, MENTAL HEALTH, AND A COMPARATIVE QUESTION ABOUT THE CURRENT PERCEPTION OF HEALTH COMPARED TO ONE YEAR AGO. THIS RESEARCH PROVED TO BE COMPREHENSIVE IN EVALUATING THE QUALITY OF LIFE OF THESE INDIVIDUALS. IT WAS OBSERVED THAT 43.3% REPORTED THAT THEIR CURRENT "HEALTH" IS RELATIVELY BETTER THAN IT WAS ONE YEAR AGO. IN QUESTIONS REGARDING WILLINGNESS AND STRENGTH IN DAILY ACTIVITIES, A PORTION OF 23.3% INDICATED THAT THEY DO NOT FEEL THESE SENTIMENTS MOST OF THE TIME. THERE WAS A DECREASE IN THE QUALITY OF TIME DEVOTED TO WORK OR OTHER ACTIVITIES, WITH 66.7% OF PEOPLE STATING THAT THIS OCCURRED, WHILE 33.3% REPORTED NOT EXPERIENCING THIS DECREASE. THIS INFORMATION ADDS IMPORTANT CONTEXT TO THE RESEARCH RESULTS REGARDING HEALTH AND THE IMPACT ON DAILY ACTIVITIES. OVERALL, THE DATA INDICATE THAT THE QUALITY OF LIFE FOR MEN AT THIS MOMENT IS BETTER THAN IT WAS A YEAR AGO, AND THERE ARE NO DIFFICULTIES IN ACTIVITIES THAT REQUIRE SIGNIFICANT EFFORT. THE RESEARCH INDICATED THAT THE HIGHER THE PERCEPTION OF QUALITY OF LIFE, THE GREATER THE PERCEPTION OF HEALTH AMONG THE SURVEYED MEN, AND FURTHERMORE, THE GREATER THE PERCEPTION OF MENTAL, SOCIAL, AND PHYSICAL COMFORT AND SATISFACTION.
Keywords: health; questionnaire; life; quality